PHYTOCHEMICAL SCREENING IN VITRO BIOLOGICAL ACTIVITIES AND ISOLATION OF ACTIVE MOLECULE FROM VITEX ALTISSIMA LEAVES - V, PREETHI NAIDU; HM, VAGDEVI; KP, LATHA; AD, AJISH (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The objective of this work is to investigate the antibacterial, anthelmintic activity of the leaves of Vitex altissima and isolation of the bioactive molecule. Methods: The agar disk diffusion method is implemented to evaluate the antibacterial activity of the plant leaves of V. altissima, using petroleum ether, ethyl acetate, and ethanol extracts. Exactly 1 mg of each extract is dissolved in 1 ml of dimethyl sulfoxide. The circular Whatman filter paper of diameter 5 mm was dipped in each extract and placed over solidified agar medium. The zone of inhibition was measured. The petroleum ether, ethyl acetate, and ethanol extracts of the plant have been used to carry out the anthelmintic activity against Indian earthworms Pheretima posthuma. The column chromatography technique is used for the isolation of bioactive molecules. Results: The results revealed that the ethyl acetate extract exhibited a remarkable zone of inhibition against Gram-positive and Gram-negative bacteria. The petroleum ether, ethyl acetate, and ethanol extracts produce zero percentage zone of inhibition against Escherichia coli bacteria. The ethanol extract showed potent anthelmintic activity. The spectral data confirm that the structure of the bioactive molecule is 4-hydroxybenzoic acid. Conclusion: The preliminary results of the study revealed that the ethyl acetate extract of the plant exhibited a broad zone of inhibition against various Gram-positive and Gram-negative bacterial strains and ethanol extract showing significant anthelmintic activity. Spectral data confirmed the structure of the bioactive molecule. The obtained bioactive molecule is responsible for exhibiting potent antibacterial activity.